Profiling STEM Literacy Among Kindergarten and Elementary School Teachers in Banten Province, Indonesia: A Descriptive Case Study - Desi Eka Nur Fitriana; Indah Juwita Sari; Ika Rifqiawati; Mila Ermila Hendriyani; Evi Amelia (International Journal of STEM Education for Sustainability, 2026)
For kindergarten and elementary school teachers to be ready to face the challenges of the 21st century, they must have STEM literacy. This study describes the definition of STEM literacy for kindergarten and elementary school teachers. This research employed a descriptive qualitative approach. By using a random sampling technique, the subjects of this research were kindergarten and elementary school teachers in Serang City, Banten, Indonesia. In this research, a STEM literacy questionnaire was employed, which consisted of three aspects: knowledge, attitudes, and skills. To gather data, a Google Form was distributed to kindergarten and elementary school teachers in Serang City. Then, the data was gathered and analyzed. The results indicate that most teachers have a good conceptual understanding of STEM as an integrative approach, but this understanding remains at a descriptive level and has not been fully implemented in learning practices. Systematic training is needed to strengthen the pedagogical implementation of STEM in a contextual and developmentally appropriate manner.